2022
DOI: 10.1186/s40104-022-00771-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibers with low hydration properties exacerbate diarrhea and impair intestinal health and nutrient digestibility in weaned piglets

Abstract: Background This study aimed to investigate the hydration properties of different-source fibrous materials by comparing their water-binding capacity (WBC), water swelling capacity (WSC), viscosity, and in vivo effects of selected samples on growth performance, nutrient digestibility, diarrhea, and intestinal health in weaned piglets. Methods A total of 13 commercially available fibrous materials were first compared in chemical composition and in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Piglets with a index > 3 diarrhea between d 1 to 28 were identified as having diarrhea. Diarrhea index = sum of diarrhea index of each group of piglets during the test period/(number of test days × number of piglets per group) [30]. At the end of the experiment (d 24 to 27), all fresh feces without urine pollution were collected twice a day at 8:00 and 20:00, and other impurities were picked out, packed into plastic sealing bags, weighed and recorded [31].…”
Section: Performance and Diarrhea Incidencementioning
confidence: 99%
“…Piglets with a index > 3 diarrhea between d 1 to 28 were identified as having diarrhea. Diarrhea index = sum of diarrhea index of each group of piglets during the test period/(number of test days × number of piglets per group) [30]. At the end of the experiment (d 24 to 27), all fresh feces without urine pollution were collected twice a day at 8:00 and 20:00, and other impurities were picked out, packed into plastic sealing bags, weighed and recorded [31].…”
Section: Performance and Diarrhea Incidencementioning
confidence: 99%
“…The present study showed that both the BP and AM groups significantly reduced the diarrhea rate. The addition of BP reduced the diarrhea rate in piglets, which may be due to the hydration properties of BP that are suitable for the fermentation of SCFAs [ 10 ]. However, the results of studies on the effect of BP groups on the diarrhea rate are inconsistent, with some studies showing no effect of BP on the diarrhea rate [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional modification is used as one of the effective tactics to improve the health and growth of weaned piglets [ 5 ], and the use of specific dietary ingredients, such as dietary fiber (DF), has been widely investigated as a way to prevent and treat diseases by modulating the gut microbiota [ 6 ]. According to its physical and chemical properties, DF can be divided into soluble dietary fiber (SDF) and insoluble dietary fiber (IDF) [ 7 ], in which beet pulp (BP), composed of SDF, such as pectin and dextran [ 8 ], has been widely used in studies on weaned piglets [ 8 , 9 , 10 ]. Alfalfa meal (AM) is a slowly fermentable IDF composed of cellulose and lignin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea rate (%) = [total number of diarrhea in each group/(experiment days × number of piglets in each group)] × 100. Diarrhea index (%) = [diarrhea score sum of each group/(experiment days × number of piglets in each group)] × 100 ( Huang et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%